2021
DOI: 10.48550/arxiv.2109.06249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ricochets on Asteroids II: Sensitivity of laboratory experiments of low velocity grazing impacts on substrate grain size

Esteban Wright,
Alice C. Quillen,
Paul Sanchez
et al.

Abstract: We compare low velocity impacts that ricochet with the same impact velocity and impact angle into granular media with similar bulk density, porosity and friction coefficient but different mean grain size. The ratio of projectile diameter to mean grain length ranges from 4 in our coarsest medium to 50 in our finest sand. Using high speed video and fluorescent markers, we measure the ratio of pre-to post-impact horizontal and vertical velocity components, which we refer to as coefficients of restitution, and the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Perhaps surface topography alone could be the culprit, since the grain size used in this work is quite large relative to the impactor. This explanation would agree with theories from Wright et al (2021), where it was suggested that as grain size relative to the projectile decreases, the response of the projectile stabilizes and becomes less dependent upon surface topography. Of course, the invisible force chain network that absorbs the impactor energy may also play a role and that impacting at a different location may change how it is able to respond.…”
Section: Impact Behavior Mappingsupporting
confidence: 89%
See 2 more Smart Citations
“…Perhaps surface topography alone could be the culprit, since the grain size used in this work is quite large relative to the impactor. This explanation would agree with theories from Wright et al (2021), where it was suggested that as grain size relative to the projectile decreases, the response of the projectile stabilizes and becomes less dependent upon surface topography. Of course, the invisible force chain network that absorbs the impactor energy may also play a role and that impacting at a different location may change how it is able to respond.…”
Section: Impact Behavior Mappingsupporting
confidence: 89%
“…To form the granular bed, the grains are allowed to fall freely and settle under Earth's gravity into the rigid bin. The interaction between all of the grains as well as the impactor are defined using a friction coefficient of = 0.85, appropriate for coarse gravel (Wright et al, 2021). A ramped acceleration-based shake is applied to the settled granular bed to further settle the system.…”
Section: Simulation Methods and Setupmentioning
confidence: 99%
See 1 more Smart Citation